2016
DOI: 10.1186/s10152-016-0456-9
|View full text |Cite
|
Sign up to set email alerts
|

Embryo brooding and its effect on feeding in the bivalve Gaimardia bahamondei Osorio & Arnaud, 1984

Abstract: Gaimardia bahamondei is a small gonochoric bivalve which lives attached to subtidal algae. Females brood their embryos in the suprabranchial region of the pallial cavity, in close proximity to the gill filaments. We found no significant difference in clearance rate between males (non-brooders) and females (brooders), regardless of the numbers of embryos in the brood, suggesting that the presence of embryos does not interfere with particle capture by the brooding female. Embryos did not ingest microalgae, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Also, Labecka and Domagala, (2016) found that Sinanodonta woodiana (Bivalvia: Unionoidea) brood eggs and developing glochidia within swollen outer demibranchs only . There had been various speculations on the adaptive advantages of brooding; include protection from unfavorable, environmental conditions and predators (Andrade-Villagrán et al, 2016). Also, it might facilitate the transfer of maternal nutrients to the developing larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Labecka and Domagala, (2016) found that Sinanodonta woodiana (Bivalvia: Unionoidea) brood eggs and developing glochidia within swollen outer demibranchs only . There had been various speculations on the adaptive advantages of brooding; include protection from unfavorable, environmental conditions and predators (Andrade-Villagrán et al, 2016). Also, it might facilitate the transfer of maternal nutrients to the developing larvae.…”
Section: Discussionmentioning
confidence: 99%